Short peptide-based cross-β amyloids exploit dual residues for phosphoesterase like activity. Issue 32 (2nd August 2022) - Mahato, Chiranjit; Menon, Sneha; Singh, Abhishek; Afrose, Syed Pavel; Mondal, Jagannath; Das, Dibyendu
Abstract : Amyloid based short peptide assemblies use antiparallel registry to expose multiple catalytic residues to bind and cleave kinetically stable phosphoester bonds of nucleic acid congeners, foreshadowing interactions of protein folds with nucleic acids. Abstract : Herein, we report that short peptides are capable of exploiting their anti-parallel registry to access cross-β stacks to expose more than one catalytic residue, exhibiting the traits of advanced binding pockets of enzymes. Binding pockets decorated with more than one catalytic residue facilitate substrate binding and process kinetically unfavourable chemical transformations. The solvent-exposed guanidinium and imidazole moieties on the cross-β microphases synergistically bind to polarise and hydrolyse diverse kinetically stable model substrates of nucleases and phosphatase. Mutation of either histidine or arginine results in a drastic decline in the rate of hydrolysis. These results not only support the argument of short amyloid peptides as the earliest protein folds but also suggest their interactions with nucleic acid congeners, foreshadowing the mutualistic biopolymer relationships that fueled the chemical emergence of life.